Bifunctional Liquid Metals Allow Electrical Insulating Phase Change Materials to Dual-Mode Thermal Manage the Li-Ion Batteries - Guo, Cong; He, Lu; Yao, Yihang; Lin, Weizhi; Zhang, Yongzheng; Zhang, Qin; Wu, Kai; Fu, Qiang (Nano-Micro Letters, 2022)
Phase change materials (PCMs) are expected to achieve dual-mode thermal management for heating and cooling Li-ion batteries (LIBs) according to real-time thermal conditions, guaranteeing the reliable operation of LIBs in both cold and hot environments. Herein, we report a liquid metal (LM) modified polyethylene glycol/LM/boron nitride PCM, capable of dual-mode thermal managing the LIBs through photothermal effect and passive thermal conduction. Its geometrical conformation and thermal pathways fabricated through ice-template strategy are conformable to the LIB’s structure and heat-conduction characteristic. Typically, soft and deformable LMs are modified on the boron nitride surface, serving as thermal bridges to reduce the contact thermal resistance among adjacent fillers to realize high thermal conductivity of 8.8 and 7.6 W m−1 K−1 in the vertical and in-plane directions, respectively. In addition, LM with excellent photothermal performance provides the PCM with efficient battery heating capability if employing a controllable lighting system. As a proof-of-concept, this PCM is manifested to heat battery to an appropriate temperature range in a cold environment and lower the working temperature of the LIBs by more than 10 °C at high charging/discharging rate, opening opportunities for LIBs with durable working performance and evitable risk of thermal runaway. Highlights: 1 The phase change materials possess conformable configuration to the structure of Li-ion batteries in macro-scale and multidirectional thermal pathways for rapid and uniform heat transfer in micro-scale. 2 Hierarchically structured phase change materials achieve dual-mode thermal management ability for heating and cooling Li-ion batteries. 3 Excellent practical battery thermal management performance was verified by 18,650 Li-ion batteries in both cold and hot environments.